Effects of increased attention allocation to threat and safety stimuli on fear extinction and its recall. (September 2021) - Klein, Zohar; Ginat-Frolich, Rivkah; Barry, Tom J.; Shechner, Tomer
Abstract: Background and objectives: Attention plays an important role in the treatment of anxiety. Increased attention to threat has been shown to yield improved treatment outcomes in anxious patients following exposure-based therapy. This study examined whether increasing attention to learned stimuli during fear extinction, an experimental analogue for exposure-based treatments, could improve extinction learning and its maintenance. Methods: Sixty-five healthy adults were randomized into experimental or control conditions. All completed a differential fear conditioning task. During extinction, a subtle attentional manipulation was implemented in the experimental group, designed to increase participants' attention to both threat and safety cues. Three days later, an extinction recall test was conducted using the original cues and two perceptually similar morphs. Results: Fear conditioning was achieved in both behavioral and psychophysiological measures. In addition, between-group differences emerged during extinction. The experimental group exhibited increased attention to stimuli and lower fear responses in physiological measure than the control group. Similarly, during extinction recall, the experimental group exhibited lower startle responses than the control group. Last, across groups, attending to the safety cue during extinction was associated with lower self-reported risk of the two generalization morphs displayed during extinction recall. Limitations: Skin conductance response (SCR) was not measured during extinction recall. Future research should include both SCR and additional generalization morphs so as to allow for the examination of more subtle individual differences. Conclusions: Results indicate that the attentional manipulation increased attention allocation to stimuli during extinction; this, in turn, affected fear-related physiological response. Highlights: A subtle attentional manipulation was implemented during extinction. The manipulation resulted in increased attention to stimuli during this phase. Increased attention during extinction influenced fear-related physiological response.